Antithymocyte globulin therapy in chronic lung allograft dysfunction - Padhye, Akhilesh Ajay; Guffey, Danielle; Leon-Pena, Andres; Segraves, Justin; Fernandez, Ramiro; Loor, Gabriel; Garcha, Puneet; Wu, Tianshi David; Li, Gloria (Frontiers in Transplantation, 2025)
IntroductionLung transplantation has seen strides in survival over the past few decades, though long-term survival remains poor. Chronic lung allograft dysfunction (CLAD) is a leading cause of graft failure and mortality beyond the first year. Anti-thymocyte globulin (ATG) is commonly used for treating refractory CLAD, though its efficacy remains uncertain.MethodsThis retrospective study evaluated the impact of ATG on lung function decline and mortality among lung transplant recipients diagnosed with CLAD, defined as a persistent >20% decline in forced expiratory volume (FEV1) from baseline. Patients treated with ATG were compared to those who did not receive ATG, using mixed effects modeling for FEV1 decline and Fine-Gray competing risk modeling for mortality.ResultsOf the 124 patients with CLAD, 55 (44%) received ATG. Administration was not associated with a significant change in FEV1 decline when compared to rate of decline prior to ATG administration [−0.0881 L/year, 95% CI (−0.21, 0.034)] or compared to non-ATG recipients [0.0599 L/year, 95% CI (−0.057, 0.18)]. However, ATG was associated with a lower hazard of all-cause mortality [subhazard ratio 0.66, 95% CI (0.39-1.14)].DiscussionWhile ATG improved survival, it did not alter lung function decline, affirming the need for prospective randomized studies.